FORMATION OF A POSITIVE STABLE MOTIVATION OF STUDENTS FOR EDUCATIONAL ACTIVITIES - Yuldashev Elyorjon Sadigovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article reveals the peculiarities of achieving educational achievements based on the formation of a positive motivation for the educational activity of students. In the process of training, theoretical and practical opinions were expressed about the motives of the training.